2015
DOI: 10.1080/15548627.2015.1052208
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3-SOD2-mROS-dependent autophagy in cadmium-induced hepatotoxicity and salvage by melatonin

Abstract: Cadmium is one of the most toxic metal compounds found in the environment. It is well established that Cd induces hepatotoxicity in humans and multiple animal models. Melatonin, a major secretory product of the pineal gland, has been reported to protect against Cd-induced hepatotoxicity. However, the mechanism behind this protection remains to be elucidated. We exposed HepG2 cells to different concentrations of cadmium chloride (2.5, 5, and 10 μM) for 12 h. We found that Cd induced mitochondrial-derived supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
198
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(214 citation statements)
references
References 66 publications
10
198
0
Order By: Relevance
“…Genetic inference or genetic knockout of SIRT3 accelerates diet-induced obesity, type 2 diabetes, and nonalcoholic fatty liver disease [8]. SIRT3 activation can deacetylate its downstream target SOD2 (also termed manganese superoxide dismutase, Mn-SOD), leading to a reduction in oxygen free radicals in the mitochondria and other subcellular organelles [12, 13]. Interestingly, the relationship between the functions of nuclear SIRT1 and mitochondrial SIRT3 is coordinated during the hypoinflammatory phase of sepsis in THP1 human promonocytes [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic inference or genetic knockout of SIRT3 accelerates diet-induced obesity, type 2 diabetes, and nonalcoholic fatty liver disease [8]. SIRT3 activation can deacetylate its downstream target SOD2 (also termed manganese superoxide dismutase, Mn-SOD), leading to a reduction in oxygen free radicals in the mitochondria and other subcellular organelles [12, 13]. Interestingly, the relationship between the functions of nuclear SIRT1 and mitochondrial SIRT3 is coordinated during the hypoinflammatory phase of sepsis in THP1 human promonocytes [29].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SIRT1 activity is decreased in the liver, spleen, small bowel, and lung tissue in experimental sepsis models, and SIRT1 activation could improve the outcome of sepsis and ameliorate the associated inflammatory response [10, 11]. Besides SIRT1, another sirtuin, SIRT3, has also received considerable attention [12, 13]. Several reports indicate that SIRT3 is exclusively located in the mitochondria and acts as an antioxidative enzyme [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hepatoprotective effect of MLT was demonstrated by Pi et al [13] when they observed increased SIRT3 protein activity and SOD2 acetylation. These findings confirm the probable hepatoprotective role of melatonin in severe fulminant hepatitis, as evidenced by Korkmaz et al [14] in the fight against ROS and reactive nitrogen species (RNS).…”
Section: Introductionmentioning
confidence: 91%
“…3A). P62 serves as a link between LC3 and ubiquitinated substrates and a reduction in the amount of p62 reflects an increase in autophagic degradation [28]. Immunoblot analysis showed that RF-EMFs treatment decreased the level of p62 (Fig.…”
Section: Autophagy Was Induced By Rfemfs Exposurementioning
confidence: 99%